PENYELESAIAN SENGKETA KONSUMEN DAN KEPASTIAN HUKUM PUTUSAN BADAN PENYELESAIAN SENGKETA KONSUMEN - Irawan, Surya; Guntara, Deny; Abas, Muhamad (Collegium Studiosum Journal, 2023)
The abstract here is a representation (not a summary) of the background, objectives, methods and conclusions. Abstract in English written in one paragraph consisting of 150- 200 words, using Times New Roman, font size 11, one space. Abstract serves to briefly present the contents of the journal. The position of consumers in general is still weak in the fields of economy, education and bargaining power, therefore it is very necessary to have laws that protect consumer interests. To be able to provide guarantees for the implementation of consumer protection, the government pours consumer protection into a legal product. This is important because only the law has the power to compel business actors to obey it, and also the law has strict sanctions. This research was conducted at the Consumer Dispute Settlement Agency domiciled in Karawang Regency using normative juridical types and approaches. The author reviews the legal literature on consumer dispute resolution and legal certainty over the Karawang Regency Consumer Dispute Settlement decision which is then collected and classified with detailed, systematic and directed records regarding documents/literature. Furthermore, the author conducts a descriptive data analysis, so that a comprehensive picture of the problems surrounding consumer dispute resolution and legal certainty is obtained for the Karawang Regency Consumer Dispute Settlement decision. The results of the research that the author conducted suggest that consumer settlement in accordance with Law No. 8 of 1999 concerning Consumer Protection can be pursued by 3 (three) methods / methods, namely, conciliation, mediation and arbitration on the basis of the choice and agreement of the parties to the dispute. The form of award by the method of conciliation and mediation shall be final and binding, without having to be asked for fiat execution to the local District Court, while the form of award taken by the method of arbitration must be requested by fiat execution to the local District Court so that the arbitral award has executory force.